Developing a local instruction theory for the scale concept: A design research study in Indonesian realistic mathematics education contextualized by Bayt Al-Qur'an Al-Akbar - Alkaff, Nazhmiah Khaalishah; Zulkardi, Zulkardi; Susanti, Ely; Meryansumayeka, Meryansumayeka (Universitas Maritim Raja Ali Haji, 2026)
Proportional reasoning is a foundational concept in middle school mathematics. However, many students struggle because they apply additive thinking rather than multiplicative reasoning when faced with abstract, formula-driven instruction. This study aims to develop and validate a local instruction theory (LIT) for the concept of Scales using the realistic context of Bayt Al-Qur'an Al-Akbar. Employing a design research methodology of the validation study type, this research engaged 39 Grade VII students in Palembang, South Sumatra, through a pilot experiment and a main field test. Data was collected through classroom observations, video recordings, and student worksheets and analyzed using a retrospective analysis method. The findings demonstrate that using the giant, non-proportional dimensions of wooden carving successfully triggered critical cognitive conflicts, prompting students to transition from informal estimates to the formal abstraction of a standardized scale factor. This study suggests that large-scale cultural architecture can serve as a tactical pedagogical intervention to subvert procedural misconceptions, offering a transferable framework for locally culture-based mathematics education globally.